The impact of maternal care on child development - Sayour, Nagham (2019)
Using a parental leave reform implemented in Canada at the end of 2000, I study the effects of an increase in maternal care on the developmental outcomes of children aged 2–3 years old. The reform increased the time mothers spent with their newborns by 3 months. Using the Canadian National Longitudinal Survey of Children and Youth, I employ a difference-in-differences methodology, where I compare children with a sibling born after the reform to those with a sibling born before the reform, relative to children of the same birth cohorts with no siblings born in the period surrounding the reform. Results show that treated children enjoy an increase of 3.6 h per week in the time they spend with their mothers, mainly due to a decrease in the time spent in non-institutional care. The increase in maternal care improves the emotional disorder score in the short-run and has no other impact on cognitive, non-cognitive or health outcomes in the short-run or the medium-run. Studying heterogeneous effects reveals a differential impact by child's age. An increase of 6.5 h per week in the time 2-year-olds spend with their mothers significantly improves their non-cognitive skills.